A 10-Year National Analysis of Pediatric Elbow Fractures. (June 2023) - Tom, Jessica E.; Eckhoff, Michael D.; Tadlock, Joshua C.; Garcia, EStephan J.
Elbow fractures comprise 15% of all fractures in children. Our study identifies risk factors and consumer products that contribute to pediatric elbow fractures. The National Electronic Injury Surveillance System was used to collect demographic and consumer product information between 2010 and 2019 for patients younger than 17 years who presented to the emergency department with elbow fractures. Of the 458, 433 elbow fractures, the average age of the patients was 7.4 ± 4.1 years and 55.6% were male children. The most common consumer product was sports and recreation equipment, followed by home furnishings. Male patients ( P < .0001) and patients 8 years and older (79.2% vs 51.1%, P < .0001) experienced significantly greater rates of injury with sports and recreation equipment. This study evaluates the products associated with pediatric elbow fractures and highlights the importance of safe sports and recreation equipment use and the role of parental counseling in preventing falls from furniture.